Three Dimensional Structural Modelling of Lipase Encoding Gene from Soil Bacterium Alcaligenes sp. JG3 Using Automated Protein Homology Analysis - Dilin Rahayu Nataningtyas; Tri Joko Raharjo; Endang Astuti (Universitas Gadjah Mada, 2019)
Bacterial lipases have significant potential to be used as the biocatalyst for many chemical reactions. In this study, a novel gene encoding lipase was isolated from an Alcaligenes sp. JG3. A pair of designed primer has successfully isolated 1 kb (LipJG3) that shares 98% identity towards lipase from Alcaligenes faecalis during sequence analysis. By using in silico tools, LipJG3 was related to the transporter protein sequences. Three highly conserved regions consisting of EASGSKT, VILLD, and LSGGQQQRVAIA were found. These regions were known as ATP-binding signature at Walker-A and Walker-B motifs and the S signature of ABC transporter family respectively. In addition, the 3-D structure of LipJG3 has been suggested but the role of the catalytic triad residues have been not fully understood.